Diversity in Risk Communication - Agung Nur Probohudono; Greg Tower; Rusmin Rusmin (Australasian Accounting, Business and Finance Journal, 2013)
This study analyses the communication of the five major categories of risk (business, strategy, market and credit risk disclosure) over the volatile 2007-2009 Global Financial Crisis (GFC) time period in key South East Asian countries’ manufacturing listed companies. This study is important as it contributes to the literature by providing insights into the voluntary risk disclosure practices using sample countries with different economic scenarios. Key findings are that business risk is the most disclosed category and strategy risk is the least disclosed. Business and credit risk disclosure consistently increase over the three year period, while operating, market and strategy risk disclosure increase in 2008, but then decrease slightly in 2009. Statistical analysis reveals that country of incorporation and size help predict risk disclosure levels. The overall low disclosure levels (26- 29%) highlight the potential for far higher communication of key risk factors.
Keywords: Voluntary risk disclosure; Asia; Agency theory; Annual Reporting